Prolonging the Cycle Life of a Lithium–Air Battery by Alleviating Electrolyte Degradation with a Ceramic–Carbon Composite Cathode. Issue 22 (17th October 2019) - Luo, Zhifu; Li, Yanyan; Liu, Zixuan; Pan, Linhai; Guan, Wanbing; Liu, Peng; Wang, Deyu
Abstract: Carbon materials with a high specific surface area are usually preferred to construct the air cathode of lithium–air batteries due to their abundant sites for oxygen reduction and discharge product growth. However, the high surface area also amplifies electrolyte degradation during charging, which would become the threshold of cyclability after addressing the issue of electrode passivation and pore clogging, but is usually overlooked in relevant research. Herein, it is proven that the critical influence of cathode surface area on electrolyte consumption by adopting carbon–ceramic composites to reduce the surface area of the air cathode. After screening several potential ceramic materials, an optimal composite of Ketjenblack (KB) and La0.7 Sr0.3 MnO3 (LSM) delivered a discharge capacity that was even higher than that of pure KB. This composite effectively mitigated the parasitic reaction current by 45 % if polarized at 4.4 V versus Li + /Li. Correspondingly, this composite prolonged the cycle life of the cell by 156 %. The results demonstrate that electrolyte consumption during charging is one of the critical boundary conditions to restrain the cyclic stability of lithium–air batteries. Abstract : Size versus durability : The influence of cathode surface area on electrolyte degradation and electrochemical performance of a lithium–air battery is investigated. An optimal composite of ketjenblack (KB) and La0.7 Sr0.3 MnO3 delivers a discharge capacity even higher than that of pure KB and mitigates the parasitic reaction current. Correspondingly, this composite prolongs the cycle life of the cell.